Uncommon cutaneous neoplasms in xeroderma pigmentosum. Case report with a 19-year follow-up. - Belloni Fortina, A.; Giulioni, E.; Alaibac, M. (European Journal of Pediatric Dermatology, 2007)
Patients with Xeroderma Pigmentosum (XP), an autosomal recessive photosensitive disorder, show an excessively high occurrence of all types of major skin cancers -basal cell and squamous cell cancer, malignant melanoma, angiomas and keratoacanthomas- in areas exposed to sunlight when compared to normal population. We report a 27-year-old XPC patient who developed in the course of the last 19 years multiple melanocytic nevi, basal cell carcinomas, malignant melanomas and several unusual benign skin tumours, i.e. angiokeratomas, trichoepitheliomas, encapsulated neuroma (solitary circumscribed neuroma) and deep penetrating nevus.